Influence of Mother Rhizome Retrieval and Organic Treatment of the Retrieved Plants on Economic Yield of Ginger at Salyan, Nepal - Basnet, M.; Gurung, H. (Journal of the Institute of Agriculture and Animal Science, 2018)
An experiment was conducted at Salyan, Nepal to assess the mother rhizome retrieval and organic treatment of the same retrieved plant on economic yield of ginger during 2015/16.‘ Kapurkot Aduwa-1’, a superior Nepalese variety was used for this experiment. Two dates i.e. 1 September and 7 September were used as a time of retrieval factor and seven organic treatments i.e. Trichoderma, Jeevatu, Bordeaux paste, mixture of neem and timur dust, vermicompost, jholmal and control as second factor and these 14 treatment combinations were laid out in factorial randomized block design with three replications. The plant height, leaf number, tiller number was found to be significantly highest with vermicompost treatment on all days 5 days interval after harvesting of the mother rhizome whereas the lowest was observed at control. The mother rhizome yield and fresh rhizome was found to be significantly highest on vermicompost applied field with 1.7 t/ha and 22.8 mt/ha respectively and lowest fresh rhizome yield (15.5. t/ha) was found with control. The disease yield was significantly lowest (0 t/ha) and highest (0.2 t/ha) with the control. Benefit cost ratio was found to be significantly highest (1.74) and lowest at control (1.32).